Penerapan Hukum terhadap Tindak Pidana Pengalihan Objek Jaminan Fidusia - Sulianto Sulianto (Postgraduate University of Merdeka Malang, 2022)
This study aims to examine the criteria for transferring fiduciary security objects into a criminal offense and the application of law in the case of criminal acts of transferring fiduciary security objects. This study is a nomrative legal research because it examines and analyzes the criteria for transferring fiduciary security objects according to the provisions of Law No. 42 of 1999 concerning Fiduciary Guarantees. The results show that there are two criteria where the act of transferring the object of fiduciary guarantee becomes a criminal offense, namely: a) The act of transferring the object of fiduciary guarantee which is carried out without the written consent of the Fiduciary Recipient. b) The act of transferring the object of fiduciary guarantee which is carried out when the fiduciary encumbrance process is not carried out jointly between the creditor and the debtor, but only based on the standard clause, namely the granting of power from the debtor to the creditor in accordance with Article 18 paragraph (1) letter h of Law No. 8 of 1999 concerning Consumer Protection.DOI: https://doi.org/10.26905/mlj.v3i2.9219